Diarrhoea-predominant IBS patients show mast cell activation and hyperplasia in the jejunum. Issue 2 (27th September 2006) - Guilarte, Mar; Santos, Javier; de Torres, Inés; Alonso, Carmen; Vicario, María; Ramos, Laura; Martínez, Cristina; Casellas, Francesc; Saperas, Esteban; Malagelada, Juan Ramón
Abstract : Background: Increased numbers of mast cells and mast cell activation in distal gut segments are associated with symptom onset and severity in irritable bowel syndrome (IBS). Although upper gut symptoms are common, mast cells have not been thoroughly evaluated in proximal gut in IBS patients. Methods: Jejunal biopsies obtained by Watson's capsule, aspiration of intestinal fluid and one blood sample were obtained in 20 diarrhoea-predominant patients with IBS (D-IBS) and 14 healthy volunteers (H). Psychological stress (Holmes-Rahe Scale) and depression (Beck's Depression Inventory) were evaluated at baseline and food and respiratory allergy excluded. Biopsies were processed for H&E staining and microscopic inflammation assessed by counting intraepithelial lymphocytes. Mast cells in lamina propria were counted by immunohistochemistry with CD117 ( c-kit ). Tryptase concentration was measured in intestinal fluid and serum. Results: D-IBS patients showed higher psychological stress than healthy volunteers (D-IBS: 203 (SD 114) v H: 112 (SD 99); p = 0.019). Immunohistochemical staining of jejunal mucosa revealed mild increase in intraepithelial CD3+ cells in D-IBS patients (D-IBS: 15.3 (SD 5.5; 95% CI 12.7 to 17.9) v H: 10.3 (SD 3.9; 95% CI 8.0 to 12.5); p = 0.006). Moreover, D-IBS patients showed marked increase in mast cells numbers (D-IBS: 34 (SD 9.3); H: 15.3 (SD 4.4) mast cells/hpf; p<0.001) and higher tryptase concentration in jejunal fluid (D-IBS: 0.45 (SD 0.38); H: 0.09 (SD 0.10) µg/l; p = 0.005). Upper gut symptoms were not associated with gender, mast cell counts, jejunal tryptase or basal stress. Conclusion: This jejunal mucosal inflammatory profile may help identify diarrhoea-predominant IBS, a stress-related disorder.